Stem Cells, Self-Renewal, and Lineage Commitment in the Endocrine System - Mariniello, Katia; Ruiz-Babot, Gerard; McGaugh, Emily C.; Nicholson, James G.; Gualtieri, Angelica; Gaston-Massuet, Carles; Nostro, Maria Cristina; Guasti, Leonardo (Frontiers in Endocrinology, 2019)
The endocrine system coordinates a wide array of body functions mainly through hormone secretion and their actions on target tissues. Over the last decades, a collective effort between developmental biologists, geneticists and stem cell biologists has generated a wealth of knowledge related to the contribution of stem/progenitor cells to both organogenesis and self-renewal of endocrine organs. The use of specific genetic mouse models, gene-discovery approaches for endocrine disorders and, more recently, reprogramming strategies to obtain functional endocrine cells, have propelled our understanding of the biology of endocrine organs. Moreover, it is now well established that pathways governing both development and stemness are frequently altered in a wide array of developmental and postnatal endocrine disorders, including cancer. Crucially, this plethora of information is being channelled into the development of potential new cell-based treatment modalities for endocrine-related illnesses, some of which have made it through clinical trials.